STUDI ANALISIS LIMBAH TERAK BESI SEBAGAI PENGGANTI SEBAGIAN AGREGAT HALUS PADA PEMBUATAN PAVING BLOCK - Anggraeni, Tetty; Septrianto, Wijaya; Supriyo, Supriyo; Fatmawati, Leily (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2017)
PT Inti General Yaja Steel Semarang is a company engaged in the metal industry, from the production activities produced waste iron slag in large quantities. On the other hand the availability of materials in the manufacture of paving blocks that are natural resources will over and can not be updated, this problem will be sought alternative replacement. The purpose of this study is the utilization of iron slag waste as a substitute of some fine aggregates in the manufacture of paving blocks, to find out the maximum compressive strength and the most efficient production cost among the mixture 1Pc : 6Ps (standard); 1Pc : 5Ps : 1Tb; 1Pc : 4Ps : 2Tb; 1Pc : 3Ps : 3Tb; 1Pc : 2Ps : 4Tb; 1Pc : 1Ps : 5Tb. Paving blocks made with size (21 x 10.5 x 6) cm. Based on the average 28-day estimate, standard paving blocks have a compressive strength of 204.09 kg/cm2, the maximum compressive strength is in the mixture of 1 PC: 3 PS: 3 TB of 335.28 kg/cm2, an increase of 64.28% of the standard paving block. While the minimum compressive strength is in the mixture of 1 PC: 1 PS: 5 TB of 195.89 kg/cm2, decreased 4.02% compared to standard paving blocks. When reviewed based on production costs, the standard paving block has a production cost of Rp 1.004,29. A mixture of 1 PC: 3 PS: 3 TB has a production cost of Rp 974,29 decreased 2.99% when compared to standard paving blocks. The most cost efficient production mix is 1 PC: 1 PS: 5 TB of Rp 894,69. Reduced by 10.91% of standard paving blocksKata kunci : compressive strength, paving block, iron slag